The role of rhetoric in charisma and leadership the case of Joseph Ejercito Estrada - Cuba, Maria Flora S. (2005)
This thesis examines the qualifications of former president Joseph Estrada's charismatic leadership and the role of presidential rhetoric in helping build his charismatic image. The research is guided by the following objectives: (1)to determine how Joseph Estrada measures up to the criteria of charismatic leadership set by Max Weber (1947) and (2) to find out the rhetoric strategies used to build a charismatic image for Joseph Estrada. Stephen McAuliff's (1982) criterion to measure charismatic leadership based on Max Weber (1947) was used to evaluate Mr. Estrada's qualification as a charismatic leader. Documentary research was conducted to analyze the factors to determine how Mr. Estrada measures up to being called a genuine charismatic leader using Stephen McAuliff's (1982) criterion to measure charismatic leadership based on Max Weber (1947). Rhetorical criticism was also employed to examine Mr. Estrada's presidential speeches. Ernest Bormann's (1982) fantasy theme analysis approach to rhetorical criticism was used as a basis for the criticism. The speeches selected for criticism were key speeches that enabled Mr. Estrada to present his agenda and vision for the country. The key speeches were examined to identify and analyze fantasy themes, fantasy types, and the rhetorical vision of Mr. Estrada using Ernest Bormann's guide questions. Six presidential speeches were analyzed: , inaugural address, first State of the Nation Address (SONA), second State of the Nation Address (SONA), third State of the Nation Address (SONA), Call for Snap Elections, and the Last Presidential Message upon Departure from Malacanang. The results of the documentary research showed that Mr. Estrada embodied personality traits that pertain to Weberian characteristics of a charismatic leader. This included a sense of mission and single-minded determination. He also enjoyed his followers' absolute emotional and cognitive identification. He also was able to establish a sense of continuity between himself and his mission and to the past legendary heroes of his culture and their mission. Mr. Estrada was also presented as the salvational or messianic leader of the poor. These personality traits Mr. Estrada possessed that pertain to charismatic leadership can however be attributed to the successful image-making strategies of his image-handlers. As image-handlers, they were primarily tasked to sustain and re-dramatize Mr. Estrada's popular movie image and established place in show business as archetypal action hero of the poor and conveniently carry it over to politics. These efforts successfully blurred the distinctions between Mr. Estrada's real and symbolic images. The poor got easily mesmerized with this blurred image of reality. In other aspects of charismatic leadership, Estrada failed. These included his ability to use traditions of society to change the norms of that society, rejection of accepted norms of administration and economics and wide freedom of decision-making. Instead, Mr. Estrada abused core Filipino values of utang ng loob, pakikisama, damayan, and the Filipino concepts of merrymaking and love for family to benefit only himself, his family, relatives, and select friends. He also employed arbitrary means of administration that violated the very laws he had sworn to uphold and protect. All these showed how Mr. Estrada merely abused the powers and privileges of the presidency and the trust placed in him by the poor. In spite of failing to use his charismatic leadership for the good of the country, the poor's unshakeable belief in Mr. Estrada persisted beyond his ouster from office and eventual arrest. This can be attributed to his presidential rhetoric. Based on the rhetoric findings, Mr. Estrada presented eleven fantasy themes that captured the imagination and expectations of the poor. He successfully portrayed himself as the Hero of the Poor, Defender of the Weak, Centennial Leader, Vilified Underdog, Graft Buster, Crime Buster, Visionary, No-Nonsense Political Leader, Tough Commander-in-Chief, and Man of Peace. Out of the eleven fantasy themes, three fantasy types emerged: Mr. Estrada as Hero of the Poor, Vilified Underdog, and Graft Buster. These fantasy themes and fantasy types helped Mr. Estrada fulfill the Erap para sa Mahirap (Erap for the Poor) rhetoric vision for the Filipino audience. This rhetoric vision led the poor to believe in Mr. Estrada's sustained symbolic image despite the contradiction of symbolic and real images of Estrada during the time the cracks of his presidency had been fully known to the public through the televised impeachment trial proceedings. In conclusion, despite Mr. Estrada's charismatic leadership which he used unethically, his followers continued to be mesmerized with the sustained, symbolic image of Estrada that catered to the imaginations and expectations of a hero the poor needed to believe in. There is a common tendency to flippantly label any highly popular contemporary leader to charismatic without carefully evaluating whether the leader truly measures up to the criteria of charismatic leadership. It is suggested that popular contemporary leaders be evaluated against such criteria in order to validate charismatic leadership. It would also be helpful to analyze the rhetoric of leaders who are commonly perceived to be charismatic because it is the message that critically binds a leader and a follower into a charismatic relationship.